Plan De Mejoramiento Industrial De La Empresa HMP MOTOR´S De La Ciudad De Barranquilla (2021)
Through this project, the design of an industrial maintenance plan for the company HMP MOTOR'S SAS was carried out, said company did not have a planned maintenance plan, a defined organizational structure and its employees were unmotivated at work, so the realization of this project. By managing the registration and control of vehicle maintenance, it was possible to improve the competitiveness and productivity of the company by 20%, likewise, procedures and functions of the processes were established in each area, stipulating specific and organized functions that maintain the employees directed towards a single objective, under their own rights and fulfilling their duties. The people who benefit from this project are all the collaborators who work in this company